2016
DOI: 10.3109/15368378.2015.1107840
|View full text |Cite
|
Sign up to set email alerts
|

Effects of electromagnetic fields on osteoporosis: A systematic literature review

Abstract: Electromagnetic fields (EMFs) as a safe, effective and noninvasive treatment have been researched and used for many years in orthopedics, and the common use clinically is to promote fracture healing. The effects of EMFs on osteoporosis have not been well concerned. The balance between osteoblast and osteoclast activity as well as the balance between osteogenic differentiation and adipogenic differentiation of bone marrow mesenchymal stem cells plays an important role in the process of osteoporosis. A number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 75 publications
2
10
0
1
Order By: Relevance
“…Finding a new treatment to promote MSC migration can bring new ideas to regenerative medicine and tissue engineering. EMF therapy has been proven to be an effective noninvasive approach in treating a wide range of bone diseases, such as fresh and nonunion fractures [ 36 , 37 ], osteoarthritis [ 38 ], and osteoporosis [ 39 41 ], both experimentally and clinically over the past decades. Our previous studies confirmed that EMF could significantly enhance the osteoblast differentiation of MSCs [ 23 , 42 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finding a new treatment to promote MSC migration can bring new ideas to regenerative medicine and tissue engineering. EMF therapy has been proven to be an effective noninvasive approach in treating a wide range of bone diseases, such as fresh and nonunion fractures [ 36 , 37 ], osteoarthritis [ 38 ], and osteoporosis [ 39 41 ], both experimentally and clinically over the past decades. Our previous studies confirmed that EMF could significantly enhance the osteoblast differentiation of MSCs [ 23 , 42 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The application of electrical fields, first explored in the 1970s, is an attractive approach in this context (Brighton et al, 1985;Kaivosoja et al, 2015;Hiemer et al, 2016). Although it is known that such electromagnetic fields can lead to osteoblast migration (Ferrier et al, 1986), foster mesenchymal osteogenic differentiation (Hronik-Tupaj et al, 2011;Hiemer et al, 2016), and have also been reported to be beneficial in view of osteoporosis prevention (Wang et al, 2016), the data base on osteoblast migration is fairly narrow (published data refer to only a few dozen cells observed), and-perhaps more importantly-the mechanisms of osteoblast activation remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…101 Additionally, the use of electromagnetic fields (EMFs) has shown curative effects in osteoporosis treatments. 102 Fathi E. et al attempt to accomplish intensified osteogenic differentiation by exposing samples to EMF whilst treating with ZnSO 4 . The samples used were the control (neither ZnSO 4 nor EMF exposure), EMF (without ZnSO 4 yet 50 Hz, 20 mT EMF exposure), ZnSO 4 (without EMF exposure yet 0.432 mg ml À1 ZnSO 4 ) and lastly EMF + ZnSO 4 (0.432 mg ml À1 ZnSO 4 and 50 Hz, 20 mT EMF exposure) and they were applied to ADSC cells.…”
Section: Composite Materials Loaded With Zinc and Strontiummentioning
confidence: 99%